Communicative and pragmatic aspects of interpreter competence (Philology, 2020)
The paper deals with the communicative and pragmatic aspects of interpreting and interpreter competence. Interpreting is seen as a communicative act that involves not only verbal interaction but also non-verbal cues and situational features. It is argued that the recognition and comprehension of those features help interpreters choose the best interpreting strategies in order to fulfill the communicative intention of the speaker. In consecutive interpreting, that choice is made on the macro level, i.e. the level of the text. It is further demonstrated that Grice’s Cooperative Principle may serve as a framework for analysing interpreting strategies in dialogue interpreting.
Keywords: interpreting; communicative competence; pragmatic competence; communicative intention; conversational maxims